Jenis dan Struktur Tema-Rema dalam Cerita Pendek “Nasehat untuk Anakku” Karya Motinggo Busye - Mujid Farihul Amin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study aims to determine what types of themes are contained in the short story "Advice for My Son" by Motinggo Busye and how the structure pattern of the teen theme is. The methodological framework consists of three strategic stages in the research, namely the data collection stage, the data analysis stage, and the data analysis result presentation stage. The results obtained from this study are that in the short story "Advice for My Son" by Motinggo Busye, there are topical / ideational themes including topical themes with markings and topical themes with markings, textual themes, and interpersonal themes. The structure of the themes contained in the short story "Advice for my Son" by Motinggo Busye is in accordance with the theme-rema theory, namely the theme is located at the beginning and the unit after the theme is rema.